No evidence for early fitness penalty in glyphosate‐resistant biotypes of Conyza canadensis: Common garden experiments in the absence of glyphosate - Zachery T. Beres; Micheal D. K. Owen; Allison A. Snow (Ecology and Evolution, 2019)
Abstract Strong selection from herbicides has led to the rapid evolution of herbicide‐resistant weeds, greatly complicating weed management efforts worldwide. In particular, overreliance on glyphosate, the active ingredient in RoundUp®, has spurred the evolution of resistance to this herbicide in ≥40 species. Previously, we reported that Conyza canadensis (horseweed) has evolved extreme resistance to glyphosate, surviving at 40× the original 1× effective dosage. Here, we tested for underlying fitness effects of glyphosate resistance to better understand whether resistance could persist indefinitely in this self‐pollinating, annual weed. We sampled seeds from a single maternal plant (“biotype”) at each of 26 horseweed populations in Iowa, representing nine susceptible biotypes (S), eight with low‐level resistance (LR), and nine with extreme resistance (ER). In 2016 and 2017, we compared early growth rates and bolting dates of these biotypes in common garden experiments at two sites near Ames, Iowa. Nested ANOVAs showed that, as a group, ER biotypes attained similar or larger rosette size after 6 weeks compared to S or LR biotypes, which were similar to each other in size. Also, ER biotypes bolted 1–2 weeks earlier than S or LR biotypes. These fitness‐related traits also varied among biotypes within the same resistance category, and time to bolting was inversely correlated with rosette size across all biotypes. Disease symptoms affected 40% of all plants in 2016 and 78% in 2017, so we did not attempt to measure lifetime fecundity. In both years, the frequency of disease symptoms was greatest in S biotypes and similar in LR versus ER biotypes. Overall, our findings indicate there are no early growth penalty and possibly no lifetime fitness penalty associated with glyphosate resistance, including extremely strong resistance. We conclude that glyphosate resistance is likely to persist in horseweed populations, with or without continued selection pressure from exposure to glyphosate.